2012
DOI: 10.2503/jjshs1.81.184
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Three Clubroot Resistance Genes through Marker-assisted Selection in Chinese Cabbage (Brassica rapa ssp. pekinensis).

Abstract: Many clubroot resistant (CR) cultivars of Chinese cabbage (Brassica rapa ssp. pekinensis) have been bred so far, but their usage is limited because the capacity for resistance breaks down with time. This degradation is caused by a pathogenic variation in the causal fungus Plasmodiophora brassicae. We attempted to accumulate 3 CR genes, CRa, CRk, and CRc, through marker-assisted selection. Five doubled haploid CR lines with an individual CR locus were used as breeding materials. The CR lines were crossed with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 18 publications
0
70
0
Order By: Relevance
“…In the present study, two markers (TCR108 and TCR79) reported by Zhang et al (2014) to be the closest markers to the CRb gene did not show linkage association with CR derived from 'Mendel'. Also, markers reported by Matsumoto et al (2012) (CRk locus) as well as those reported by Hirai et al (2004) and Saito et al (2006) We estimated the physical distances between the four previously reported clubroot resistance loci on the A3 chromosome of B. rapa. The SCAR marker HC688 reported to be linked to the CRk gene ) was positioned at 14,396,950-14,397,879 nt, the STS marker OPC11-2S reported to be linked to the Crr3 gene (Hirai et al 2004) was located at 15,238,429-15,239,385 nt, the marker TCR31 (TCR108 did not amplify genomic DNA in our population) reported to be linked to the CRb gene (Zhang et al 2014) was positioned at 23,790,671-23,793,046 nt, and the SCAR marker GC2360 reported to be linked to the CRa gene ) located at 24,577,326-24,577,423 nt on the A3 chromosome of B. rapa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, two markers (TCR108 and TCR79) reported by Zhang et al (2014) to be the closest markers to the CRb gene did not show linkage association with CR derived from 'Mendel'. Also, markers reported by Matsumoto et al (2012) (CRk locus) as well as those reported by Hirai et al (2004) and Saito et al (2006) We estimated the physical distances between the four previously reported clubroot resistance loci on the A3 chromosome of B. rapa. The SCAR marker HC688 reported to be linked to the CRk gene ) was positioned at 14,396,950-14,397,879 nt, the STS marker OPC11-2S reported to be linked to the Crr3 gene (Hirai et al 2004) was located at 15,238,429-15,239,385 nt, the marker TCR31 (TCR108 did not amplify genomic DNA in our population) reported to be linked to the CRb gene (Zhang et al 2014) was positioned at 23,790,671-23,793,046 nt, and the SCAR marker GC2360 reported to be linked to the CRa gene ) located at 24,577,326-24,577,423 nt on the A3 chromosome of B. rapa.…”
Section: Discussionmentioning
confidence: 99%
“…The genomic DNA of the parents and the bulks were screened with 370 (212 A ? 158 C) Brassica SSR markers obtained from Agriculture and AgriFood Canada (AAFC) through a material transfer agreement, one RAPD marker (Diederichsen et al 2006), two SSR markers flanking the CR locus of A3 and two markers from C3 linkage groups of Werner et al (2008), and 72 published markers reported to be linked to the nine published CR loci: the CRa (Matsumoto et al 1998Hayashida et al 2008;Ueno et al 2012), CRb (Piao et al 2004, Zhang et al 2014, CRb Kato (Kato et al 2012(Kato et al , 2013, CRk and Crr3 (Hirai et al 2004;Saito et al 2006) on A3, CRc on A2 Matsumoto et al 2012), Crr1, Crr2 and Crr4 on A8, A1 and A6, respectively (Suwabe et al 2003. For convenience of reference to the molecular markers and discussion, the locus reported by Kato et al (2012Kato et al ( , 2013 will be referred hereafter as CRb Kato .…”
Section: Dna Extraction Pcr Amplification and Electrophoresismentioning
confidence: 99%
See 1 more Smart Citation
“…Strategies such as resistance gene pyramiding may help to increase the durability of resistance. For example, the presence of three resistance genes in Chinese cabbage has enhanced the durability of CR in this crop (Matsumoto et al ., ). Furthermore, more genes may be identified given the many sources of resistance in turnips.…”
Section: Introductionmentioning
confidence: 97%
“…Although there are some commercial clubroot-resistant (CR) canola and cabbage cultivars available, this resistance is associated with single dominant CR genes [11], as reported in Chinese cabbage [12] and oilseed rape [13], and leads to rapid breakdown. Two resistance genes have been isolated from Chinese cabbage ( Brassica rapa), CRa and Crr1 [14,15], while genetic mapping and identification of clubroot resistance has been also achieved in Brassica oleracea [1619].…”
Section: Introductionmentioning
confidence: 99%